Criminalization Based on the Principle of Human Rights Limitation - Mahrus Ali; Irwan Hafid; Kurnia Dewi Anggraeny (Universitas Ahmad Dahlan, 2022)
Introduction to The Problem: The use of criminal law to limit the freedom of citizens’ civil rights must be done with caution since it intimately links to the infringement of such rights.Purpose/Objective Study: The present study aims to explore the criteria of criminalization based on the principle of limitations of human rights.Design/Methodology/Approach: This study employed doctrinal legal research using both conceptual and statutory approachesFindings: In the policy formation of illegal acts, the legislator frequently formulates rights constraints. The criminalization criteria specified in the human rights limitation can be used to apply this restriction. Restriction-containing offenses determined by the legislature must be by law, legitimate aim, and necessity in a democratic society. A consistent model of criteria for democratic society demands does not exist. This last criterion is linked to both the proportionality principle in human rights and the concept of criminal law as a last resort.Paper Type: Research Article